Effectiveness of Scientific Calculators’ Usage in the Teaching and Learning of Grade 11 Parabola Functions to Improve Learner Performance - Ogunsipe, Olugbenga Adebayo; Makgakga, Tšhegofatšo Phuti (Research in Social Sciences and Technology- OpenED Network, 2024)
The use of scientific calculators in teaching parabola functions has been shown to have significant effect in learner performance. This study examined the effectiveness of scientific calculators’ usage in the teaching and learning of Grade 11 parabola functions to improve learner performance. Bandura’s observational learning theory underpinned this study. A non-equivalent quazi-experimental design was espoused to collect data from the experimental and control groups. A pre-test and a post-test were administered to both experimental group and control group in the same day and at the same time, to avoid contamination of results. Wilcoxon-Rank sum test was used to determine the significant difference between the two study groups. The results showed that the experimental group performed significantly better than the control groupin the post-test after the implementation of scientific calculators in teaching parabola functions. The study suggests that scientific calculators can be used to teach parabola functions to improve learner performance and advance teacher content knowledge, pedagogical content knowledge and professional development.